Organization and content efficiency substantiation of a strengthened professional and applied physical training course for railway higher educational institution students - Anzhelika Yefremova; Liudmyla Shesterova (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to experimentally substantiate the effectiveness of the application of the experimental program for physical education with an intensified course of professional-applied physical training (PAPT) for students of I-II courses of railway specialties. Material & Methods: analysis and generalization of literary sources, pedagogical experiment, pedagogical testing, physiological and psycho-physiological methods, methods of mathematical statistics. Result: obtained data after the introduction of the experimental program on physical education with an intensified course of professional-applied physical training, students of railway universities. Conclusion: analysis and generalization of the literature sources found the absence of a scientifically based program of PAPT for students of higher education institutions of the railway profile. The introduction in the educational process of physical education of the experimental program on physical education with the strengthened course of the PAPT showed an increase in the level of physical, professionally applied physical and psycho-physiological readiness of students.